Self-service technology (SST) towards guest satisfaction in hotel industry / Siti Asura Mohd Ismail and Intan Juliyani Zainal - Mohd Ismail, Siti Asura; Zainal, Intan Juliyani (2017)
Self-service technologies (SSTs) are changing the way customers interact with companies to create service outcomes. SSTs also use in other industry such as retailing, manufacturing and internet banking. The purpose of this to determine the relationship between SSTs (electronic kiosk, internet, video/cd and telephone) towards guest satisfaction. Customer satisfaction was operationalized in terms of hotel atmosphere and hospitality. By using secondary data, the researchers get the information on previous journals. By implementing SSTs can help the hotel industry in improving their service in order to satisfy their guest. This study also contributed to academic platform on valuable information about current trends. Finally, this study ends up with by suggestion and useful implications for hotel industry.